Istilah Kekerabatan pada Bahasa Sangihe (Suatu Kajian Linguistik Antropologi) - Patimbano, Lidya Grace Lineke; Imbang, Djeinnie; Senduk, A. G. (Kajian Linguistik, 2017)
Language is a communication tool that has an important role to convey information. Languange is also a sound alert system that agreed to be used by members of certain communities work togather, communicate andÂ  identifying themselves. The background of this study by the term kinship tends to do with the concept of culture used by certain people who call someone in the family as in the community Sangihe. These factors that the attention ofÂ  researchers to the term of kinship in the society. The purpose of this study is to indentify kinship term in the Sangihe Society and explain the meaning of kinship in the Sangihe sociey that reflect of culture.The method used in this research is descriptive qualitative method. To obtain the data in the field. Burling theory (1970) to answer the first question and the theory Spradley (1979) and Casson (1981) to answer the second question. To obtain the data in the field, researchers used a method refer and method capable (SBCL) and using the questionnaire in the form of a questionnaire of Sudaryanto (1993) and interview techniques as recommended by Spradley (1997), which consists of general questions, specific questions, sample questions, questions based on experiences and questions native language or dialect. These data are then captured and recorded. In the data analysis methods, used analysis of the concept of expression to identify and explain the data as a whole, on the basis of linguistic theory of cultural anthropology discover the meaning behind the kinship terms on Sangihe society.